2022
DOI: 10.3390/pathogens11101200
|View full text |Cite
|
Sign up to set email alerts
|

Tight Junctions, the Key Factor in Virus-Related Disease

Abstract: Tight junctions (TJs) are highly specialized membrane structural domains that hold cells together and form a continuous intercellular barrier in epithelial cells. TJs regulate paracellular permeability and participate in various cellular signaling pathways. As physical barriers, TJs can block viral entry into host cells; however, viruses use a variety of strategies to circumvent this barrier to facilitate their infection. This paper summarizes how viruses evade various barriers during infection by regulating t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 101 publications
0
11
0
Order By: Relevance
“…Histological examination revealed that apical SARS-CoV-2 inoculation (upper Transwell inoculation) triggers epithelial layer degeneration and live viruses emerged in the lower Transwell chamber, indicating that intercellular proteins junctions are damaged and no longer act as a barrier. Furthermore, there are numerous pieces of evidence that SARS-CoV-2 infection disrupts tight junctions by metallopeptidases in the intestinal epithelium and Caco-2 monolayer[2,24,46,47] crossing the intestinal epithelial barriers by paracellular trafficking, as previously reported with other viruses[4850]. It is also worth noting that the cellular receptor for SARS-CoV, angiotensin-converting enzyme 2 (ACE2), is located on the apical plasma membrane of polarized epithelial cells and mediates infection from the apical side of these cells[51].…”
Section: Discussionmentioning
confidence: 75%
“…Histological examination revealed that apical SARS-CoV-2 inoculation (upper Transwell inoculation) triggers epithelial layer degeneration and live viruses emerged in the lower Transwell chamber, indicating that intercellular proteins junctions are damaged and no longer act as a barrier. Furthermore, there are numerous pieces of evidence that SARS-CoV-2 infection disrupts tight junctions by metallopeptidases in the intestinal epithelium and Caco-2 monolayer[2,24,46,47] crossing the intestinal epithelial barriers by paracellular trafficking, as previously reported with other viruses[4850]. It is also worth noting that the cellular receptor for SARS-CoV, angiotensin-converting enzyme 2 (ACE2), is located on the apical plasma membrane of polarized epithelial cells and mediates infection from the apical side of these cells[51].…”
Section: Discussionmentioning
confidence: 75%
“…The function of tight junctions is challenged by a variety of factors, including toxins, pathogens, or inflammation and cancer, which can lead to a loss of barrier integrity and finally to tissue damage [ 46 , 47 , 48 , 49 ]. Both the loss and assembly of tight junctions are regulated by numerous signaling pathways that involve a great variety of molecules, including protein kinases, phosphatases, G-proteins, and the regulators of their expression at both mRNA and protein levels [ 50 , 51 ].…”
Section: Mirnas Evs and Physical Barriersmentioning
confidence: 99%
“…SARS-CoV-2 entrance in the epithelium is favored when the integrity of tight junctions (TJ), which are formed between neighboring cells and regulate the passage of ions and other small solutes, is altered. During the analysis of TJs in lung epithelial cells, the virus was found to affect the integrity of lung epithelial cells [ 83 ]. Additionally, the blood-brain barrier can be disturbed by SARS-CoV-2 and lead to derangements of tight junction and adherens junction proteins [ 84 ].…”
Section: Implications Of Altered Molecular Processes In Long Covid Sy...mentioning
confidence: 99%